Response of four tropical legumes and alfafa to varying levels of sulfur - Jones, Milton B.; Quagliato, João L. (Pesquisa Agropecuaria Brasileira, 2014)
Four tropical legumes and alfafa were grown on a sulfur deficient soil in the greenhouse with various rates of S applied. Plants were harvested at three dates and total S and N determined on harvested plant material. The first fully matured leaves were sampled for sulfate-sulfur determination at two dates. All of the species tested increased in dry matter production as the supply of S increased. However, the time at which the response occurred and the magnitude of the responses were different for each species. Total S and sulfate-S concentrations in the tropical legumes were generally higher and varied less than in alfafa. Total S value decreased less with time than SO4-S values. Nitrogen concentration tended to increase with increasing levels of applied S.